Surface-Based Amplitude of Low-Frequency Fluctuation Alterations in Patients With Tinnitus Before and After Sound Therapy: A Resting-State Functional Magnetic Resonance Imaging Study - Wei, Xuan; Lv, Han; Chen, Qian; Wang, Zhaodi; Zhao, Pengfei; Liu, Chunli; Gong, Shusheng; Yang, Zhenghan; Wang, Zhenchang (Frontiers in Neuroscience, 2021)
This study aimed to investigate abnormal tinnitus activity by evaluating brain surface-based amplitude of low‐frequency fluctuation (ALFF) changes detected by resting‐state functional magnetic resonance imaging (RS‐fMRI) in patients with idiopathic tinnitus before and after 24 weeks of sound therapy. We hypothesized that sound therapy could gradually return cortical local brain function to a relatively normal range. We recruited thirty-three tinnitus patients who had undergone 24 weeks of sound therapy and twenty-six matched healthy controls (HCs). For the two groups of subjects, we analyzed the spontaneous neural activity of tinnitus patients by cortical ALFF and detected its correlation with clinical indicators of tinnitus. Two-way mixed model analysis of variance (ANOVA) and Pearson’s correlation analysis were used in the statistical analysis. Student-Newman-Keuls (SNK) tests were used in the post hoc analysis. Interaction effects between the two groups and between the two scans revealing local neural activity as assessed by ALFF were observed in the bilateral dorsal stream visual cortex (DSVC), bilateral posterior cingulate cortex (PCC), bilateral anterior cingulate and medial prefrontal cortex (ACC&MPC), left temporo-parieto-occipital junction (TPOJ), left orbital and polar frontal cortex (OPFC), left paracentral lobular and mid cingulate cortex (PCL&MCC), right insular and frontal opercular cortex (IFOC) and left early visual cortex (EVC). Importantly, local functional activity in the left TPOJ and right PCC in the patient group was significantly lower than that in the HCs at baseline and was increased to relatively normal levels after treatment. The 24-week sound therapy tinnitus group demonstrated significantly higher ALFF in the left TPOJ and right PCC than in the tinnitus baseline group. Also, compared with the HC baseline group and the 24-week HC group, the 24-week sound therapy tinnitus group demonstrated slightly lower or higher ALFF in the left TPOJ and right PCC, and there were no significant differences between the 24-week sound therapy tinnitus and HC groups. Thus, sound therapy can change auditory, vision, cognitive control and emotional processing, and surface-based RS-fMRI is a more sensitive method to judge local functional activity than other methods.